The Role of Uncitral in Standardizing International Project Contracts and Its Implementation in Indonesia - Egit Bobyarta; Sarwono Hardjomuljadi; Sami'an Sami'an; Anik Kunantiyorini (International Journal Labs, 2026)
The globalization of cross-border construction projects increases the need for legal certainty and uniformity in the arrangement of international construction contracts. Differences in national legal systems, the complexity of long-term projects, and the dynamics of technical and economic risks often lead to contractual imbalances and potential disputes. In this context, UNCITRAL plays an important role through the development of soft law international legal instruments, especially the UNCITRAL Legal Guide on Drawing Up International Contracts for the Construction of Industrial Works, which provides a principled normative framework for the design of international construction contracts. This study aims to analyze the role of UNCITRAL in the standardization of international construction contracts and examine the implementation of these principles in construction contract practices in Indonesia, taking into account the development of national contract standards regulated in the Regulation of the Government Goods/Services Procurement Policy Institute Number 4 of 2024 and the Regulation of the Minister of Public Works and Public Housing Number 25 of 2020. The research method used is normative legal research with a legislative, conceptual, and analytical approach to UNCITRAL instruments and relevant national regulations. The results show that UNCITRAL functions as a normative framework that emphasizes procedural clarity, proportionate risk allocation, contract adaptation to changing circumstances, and a tiered dispute resolution mechanism.